2019
DOI: 10.1080/00313831.2019.1639814
|View full text |Cite
|
Sign up to set email alerts
|

Educational Experiences and Perceptions of Occupational Hierarchies: The Case of the Norwegian Working Class

Abstract: In this article we present the experiences of members of the Norwegian working class in the educational system and show that the findings contradict established theories in the sociology of education in a way that calls for a re-examination of the function of societal hierarchies in such studies. Secondly, we report how working-class individuals comprehend society's valuation of their work and whether these experiences affect their own judgments and evaluations of work. The findings reveal an enlightened worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, similar studies from elsewhere inform us that the social dynamics reported in our article occur across Norway. In an ongoing study of the Norwegian working class, with interviews done in Bergen, Kristiansand and Oslo, Skarpenes and Sakslind (forthcoming; see also Skarpenes, 2017) document much the same indifference and autonomy as we have in Stavanger. At ‘the other end’ of the discursive gap, too, other Norwegian studies report much the same findings as we do.…”
Section: Interpretations: Cultural Repertoires Shifts Of Values Socmentioning
confidence: 76%
“…However, similar studies from elsewhere inform us that the social dynamics reported in our article occur across Norway. In an ongoing study of the Norwegian working class, with interviews done in Bergen, Kristiansand and Oslo, Skarpenes and Sakslind (forthcoming; see also Skarpenes, 2017) document much the same indifference and autonomy as we have in Stavanger. At ‘the other end’ of the discursive gap, too, other Norwegian studies report much the same findings as we do.…”
Section: Interpretations: Cultural Repertoires Shifts Of Values Socmentioning
confidence: 76%
“…Our data do not enable enquiry into this explanation. Its relevance may be considerable, however, as there are indications that many, especially in privileged social strata, assign little esteem to, but rather look down upon, the low educated (see, for example, Abrassart & Wolter, 2020;Sandel, 2020;Skarpenes & Sakslind, 2020).…”
Section: Discreditmentioning
confidence: 99%
“…We do not have hard data to support the argument, but we still might launch a hypothesis that there is an ongoing process in which political, scientific, and journalistic arguments and values mingle and mix and establish what can be called the paternalistic narrative. The narrative or the values associated with it are embedded in the working-class culture and sometimes influence the class's (especially women) perception of itself (Skarpenes and Sakslind 2018). We know from a classical study of women in the working class in Britain that feelings of inferiority are present, in the sense that shame and a desire to appear respectable is common (Skeggs 1997).…”
Section: The Norwegian Working Class: Educational and Occupational Famentioning
confidence: 99%
“…Where Hoel mainly identified pride in her study of women from the 80s, we can register, in addition to pride, a certain resignation and anger among some of these women, as a response to their placement at the lower end of the occupational hierarchy. (Skarpenes and Sakslind 2018)…”
Section: The Norwegian Working Class: Educational and Occupational Famentioning
confidence: 99%
See 1 more Smart Citation